PENGARUH LIMBAH CAIR PABRIK GULA DI KEDIRI TERHADAP PERTUMBUHANTANAMAN ECENG GONDOK (Eichornia crassipes). - Reni Bekti Anila; Arum Sanjayanti; Sulistiono Sulistiono; Inggit Tria Prameswari (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2014)
Kediri is an industrial town in which the industry has become main commodity livelihood for its citizen. The rapid of technology encourages the growth of industries that have great contribution for environmental pollution; one of them is sugar factory in Kediri. This factory produces liquid waste that it contains organic and un-organic compounds which its presence trigger Eichornia Crassipes grows rapidly in the river. In addition, Eichomia Crassipes has a potential as an Agnesia cleaners. This study is aimed at determining the effect of sugar factory liquid waste to the growth of Eichornia Crassipes. True experimental type RAK was selected as a research design, in which the treatment was done by 0% (as control), 25%, 50%, 75%, and 100% and it was repeated 5 times. Observed parameter included root length, stem length, length and width of leaf. The systematic data was analyzed using STAT program version 2.6. the results showed significant differences in the growth of the Eichornia Crassipes  morphology on root length, stem length, length and width of leaf width and the 100 % liquid waste of sugar factory  highest average was found on the length root of stalk. On the other side, liquid waste of sugar’s factory can be used as an organic fertilizer to some extent (deposited waste). Keywords: Eichornia Crassipes, liquid waste, morphological structure